Role of dynamic environmental change in sustaining the protracted process of rice domestication in the lower Yangtze River. (15th August 2020) - He, Keyang; Lu, Houyuan; Zheng, Hongbo; Yang, Qing; Sun, Guoping; Zheng, Yunfei; Cao, Yeting; Huan, Xiujia
Abstract: Recent increases in archaeobotanical and genetic evidence offer insights into agricultural origins and plant domestication, which suggest a protracted process taking thousands of years that began by 10, 000 cal a BP or in the late Pleistocene. Compared to the cereal domestication that was accomplished in the early Holocene in Southwest Asia and Mesoamerica, the reasons for the delay in rice domestication in China until the middle Holocene remain unclear. In the present study, the dynamic influence of environmental change on rice domestication was revealed by evidence from sedimentary facies and phytolith analysis of the high-resolution HMD1602 core from the Hemudu site. Rice phytoliths were recovered from beneath the neritic sediment at this site for the first time, which pushes the history of human activities and the process of rice domestication in the Yaojiang Valley back to 8200-7600 cal a BP. The process of rice domestication at the Hemudu site developed discontinuously with an obvious interruption during 7600-7100 cal a BP, which was significantly influenced by marine transgression and palaeo-typhoon events. Furthermore, synthesis of palaeoenvironmental and archaeobotanical records suggests that rice exploitation and domestication was interrupted three times during 13, 000-10000, 7900-7400 and 6400-5600 cal a BP, respectively. The first interruption of rice exploitation was induced by the Younger Dryas, which triggered the onset of cultivation at approximately 10, 000 cal a BP in Southwest Asia and China, while the second two interruptions of rice domestication were caused by marine transgressions, which postponed the domestication of only rice. Therefore, the delayed accomplishment of rice domestication until the middle Holocene resulted from an unstable climatic environment and sea-level fluctuations, which ultimately led to the discontinuous process of rice domestication. Highlights: Rice recovered beneath the neritic sediment for the first time in the Hemudu site. Rice domestication developed discontinuously since 8200 BP in the Yaojiang Valley. Three interruption events of rice exploitation and domestication were recognized in the Yangtze River. Combined effects of climate and sea-level fluctuation protracted rice domestication.